INTRAOPERATIVE DETECTION OF SENTINEL LYMPH NODES USING INFRARED IMAGING SYSTEM IN LOCAL NON-SMALL CELL CARCINOMA OF LUNG - A. L. Akopov; G. V. Papayan; I. V. Chistyakov; A. .. Karlson; A. V. Gerasin; A. S. Agishev (Вестник хирургии имени И.И. Грекова)
The article presents the results of the first domestic experience of intraoperative fluorescence mapping of sentinel lymph nodes in lung cancer. The research included 10 patients, who underwent surgery over the period of time from September 2013 to May 2014. After performing thoracotomy, the solution of indocyanine green (ICG) was injected using subpleural position above the tumor in 3-4 points. Fluorescence (ICG) image guided surgery was carried out by using infrared radiation (wave length 808 nm) on lung surface, root of lung, mediastinum in real time. Fluorescence lymph nodes were mapped. In case that metastatic lesions weren’t revealed in sentinel lymph nodes, they weren’t noted in other nodes. Method specificity consisted of 100%. Biopsy and histological study of sentinel lymph nodes mapped during fluorescence (ICG) image guided surgery could be useful for prevention of lymphodissection in patients with non-small cell carcinoma of lung.